Multicountry survey of emergency and critical care medicine physicians' fluid resuscitation practices for adult patients with early septic shock. Issue 7 (7th July 2016) - McIntyre, Lauralyn; Rowe, Brian H; Walsh, Timothy S; Gray, Alasdair; Arabi, Yaseen; Perner, Anders; Gordon, Anthony; Marshall, John; Cook, Deborah; Fox-Robichaud, Alison; Bagshaw, Sean M; Green, Robert; et al.
Abstract : Objectives: Evidence to guide fluid resuscitation evidence in sepsis continues to evolve. We conducted a multicountry survey of emergency and critical care physicians to describe current stated practice and practice variation related to the quantity, rapidity and type of resuscitation fluid administered in early septic shock to inform the design of future septic shock fluid resuscitation trials. Methods: Using a web-based survey tool, we invited critical care and emergency physicians in Canada, the UK, Scandinavia and Saudi Arabia to complete a self-administered electronic survey. Results: A total of 1097 physicians' responses were included. 1 L was the most frequent quantity of resuscitation fluid physicians indicated they would administer at a time (46.9%, n=499). Most (63.0%, n=671) stated that they would administer the fluid challenges as quickly as possible. Overall, normal saline and Ringer's solutions were the preferred crystalloid fluids used 'often' or 'always' in 53.1% (n=556) and 60.5% (n=632) of instances, respectively. However, emergency physicians indicated that they would use normal saline 'often' or 'always' in 83.9% (n=376) of instances, while critical care physicians said that they would use saline 'often' or 'always' in 27.9% (n=150) of instances. Only 1.0% (n=10) of respondents indicated that they would use hydroxyethyl starch 'often' or 'always'; use of 5% (5.6% (n=59)) or 20–25% albumin (1.3% (n=14)) was also infrequent. The majority (88.4%, n=896) of respondents indicated that a large randomised controlled trial comparing 5% albumin to a crystalloid fluid in early septic shock was important to conduct. Conclusions: Critical care and emergency physicians stated that they rapidly infuse volumes of 500–1000 mL of resuscitation fluid in early septic shock. Colloid use, specifically the use of albumin, was infrequently reported. Our survey identifies the need to conduct a trial on the efficacy of albumin and crystalloids on 90-day mortality in patients with early septic shock.